2010
DOI: 10.1016/j.jconrel.2009.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Lesion complexity determines arterial drug distribution after local drug delivery

Abstract: Though stents are deployed in diseased arteries drug distribution has only been quantified in intact, non-diseased vessels. We correlated steady-state arterial drug distribution with tissue ultrastructure and composition, in abdominal aortae from atherosclerotic human autopsy specimens and rabbits with lesions induced by dietary manipulation and controlled injury. Paclitaxel, everolimus, and sirolimus deposition in human aortae was maximal in the media and scaled inversely with lipid content. Net tissue paclit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 49 publications
(53 reference statements)
1
51
1
1
Order By: Relevance
“…Their simple model of plaque suggested that the plaque could act as a reservoir for the drug, ensuring that patients with a higher degree of atherosclerosis may receive therapeutic levels of drug for longer than those with a lesser degree of plaque. This finding is in contrast to an experimental study in the literature (Tzafriri et al, 2010) where it was concluded that drug concentration was inversely correlated to lipid concentrations. The McGinty et al model did, however, neglect the intimal region of the arterial wall and the endothelium layer of cells.…”
Section: One-dimensional Modelscontrasting
confidence: 99%
See 1 more Smart Citation
“…Their simple model of plaque suggested that the plaque could act as a reservoir for the drug, ensuring that patients with a higher degree of atherosclerosis may receive therapeutic levels of drug for longer than those with a lesser degree of plaque. This finding is in contrast to an experimental study in the literature (Tzafriri et al, 2010) where it was concluded that drug concentration was inversely correlated to lipid concentrations. The McGinty et al model did, however, neglect the intimal region of the arterial wall and the endothelium layer of cells.…”
Section: One-dimensional Modelscontrasting
confidence: 99%
“…McGinty et al seem to be the only authors who have attempted to model the plaque to date, although (Tzafriri et al, 2010) have experimentally examined the effect of the plaque. The plaque is known to contain a fibrous cap of variable thickness as well as a necrotic core made up of cellular debris, cholesterol cleft and cell membranes.…”
Section: Inclusion Of the Endothelium Intima And Plaquementioning
confidence: 99%
“…Not only does the degree of disease influence how a single drug is absorbed, these differences are not uniform and differ between antiproliferatives. 49 How plaque morphology influences drug uptake and how these differences affect drug efficacy remains to be determined. As such, one can portend the need for better "lesion stratification," either with advanced imaging modalities or with molecular techniques to identify the ideal antiproliferative for a specific lesion.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several parameters are involved in this process: the nature of the drug and of the polymer, the stent design and the blood flow in this area. In vitro [2][3][4] and in vivo studies [5][6][7] have highlighted the role of the coating, the drug, its concentration, the drug release kinetics in transporting the drug towards the arterial wall. Nevertheless these studies often give only qualitative information and are for some of them not directly usable for the optimization of DES.…”
Section: Introductionmentioning
confidence: 99%